The exercise-induced inflammatory response in inflammatory bowel disease: A systematic review and meta-analysis. - Kelly A Baker; Timothy D Miller; Frank E Marino; Tegan E Hartmann (PLoS ONE)
Background This study investigated selected inflammatory responses to acute and chronic exercise in individuals with inflammatory bowel disease (IBD). Methods A systematic review and meta-analysis was conducted on all relevant exercise-based intervention publications with IBD participants. The study included articles that utilised a broad range of acute and chronic exercise interventions, with inflammatory biomarkers measured and symptoms documented, both pre- and post-exercise for those with IBD. The search was limited to studies published in English, the use of human participants, and primary studies, with no restrictions on date of publication or participant's age. Articles were retrieved through the electronic databases: PubMed, SPORTDiscus, and Scopus. This study adhered to Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Results Six inflammatory markers were included in the meta-analysis which consisted of five studies. Exercise interventions resulted in no significant difference in IL-6 (SMD = -0.09; 95% CI = -0.49, 0.30; P = 0.64), TNF-α (SMD = 0.08; 95% CI = -0.31, 0.48; P = 0.68), CRP (SMD = -0.04; 95% CI = -0.58, 0.50; P = 0.89), IL-17 (SMD = 0.15; 95% CI = -0.45, 0.76; P = 0.62), leukocytes (SMD = 0.40; 95% CI = -0.53, 1.33; P = 0.40) or lymphocytes (SMD = 0.32; 95% CI = -0.33, 0.97; P = 0.33), thus, indicating exercise may have no effect on inflammatory markers in IBD. Bowel symptoms improved following regular moderate exercise that incorporated stress management. Conclusion Heterogeneity among the identified literature may have led to exercise interventions being ineffective in reducing inflammation. Although the limited number of eligible studies may reduce the reliability of results, it emphasises the need for additional research in this domain. Importantly, no adverse symptomatic responses to exercise indicate that exercise is safe for IBD patients.